Beyond alliances : the Jewish role in reshaping the racial landscape of Southern California - Ansell, Lisa; Sanchez, George J.; Zuckerman, Bruce (Jewish role in American life, 2012)
This volume focuses on the unique and special role that Jews took in reshaping the ethnic/racial landscape of Southern California in the mid-twentieth century, roughly from 1930 to 1970.